2020
DOI: 10.1186/s13046-020-1541-0
|View full text |Cite
|
Sign up to set email alerts
|

FKBP9 promotes the malignant behavior of glioblastoma cells and confers resistance to endoplasmic reticulum stress inducers

Abstract: Background: FK506-binding protein 9 (FKBP9) is amplified in high-grade gliomas (HGGs). However, the roles and mechanism(s) of FKBP9 in glioma are unknown. Methods: The expression of FKBP9 in clinical glioma tissues was detected by immunohistochemistry (IHC). The correlation between FKBP9 expression levels and the clinical prognosis of glioma patients was examined by bioinformatic analysis. Glioblastoma (GBM) cell lines stably depleted of FKBP9 were established using lentiviruses expressing shRNAs against FKBP9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 38 publications
1
21
0
1
Order By: Relevance
“…A recent study has found that FKBP9 could be an independent prognostic marker for predicting the poor prognosis of patients with prostate cancer; that high FKBP9 levels and short biochemical-recurrence-free survival are significantly correlated ( p = 0.041); and that FKBP9 may be a cancer promoter that enhances prostate cancer progression ( Jiang et al, 2020 ). Another study found that FKBP9 is a critical factor for promoting the malignant behaviors of glioblastoma cells; high FKBP9 level is related to poor prognosis and could confer malignant cells with the capability to resist endoplasmic reticulum stress inducers ( Xu et al, 2020 ). Other studies have also confirmed that FKBP9 is connected with other cancers, such as colorectal and breast cancers ( Bianchini et al, 2006 ; Chang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has found that FKBP9 could be an independent prognostic marker for predicting the poor prognosis of patients with prostate cancer; that high FKBP9 levels and short biochemical-recurrence-free survival are significantly correlated ( p = 0.041); and that FKBP9 may be a cancer promoter that enhances prostate cancer progression ( Jiang et al, 2020 ). Another study found that FKBP9 is a critical factor for promoting the malignant behaviors of glioblastoma cells; high FKBP9 level is related to poor prognosis and could confer malignant cells with the capability to resist endoplasmic reticulum stress inducers ( Xu et al, 2020 ). Other studies have also confirmed that FKBP9 is connected with other cancers, such as colorectal and breast cancers ( Bianchini et al, 2006 ; Chang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, STAT3 and CDK6 have been associated with cancer-associated fibroblast and immune cell infiltration and are considered biomarkers of poor prognosis in multiple cancers [ 23 ]. Furthermore, our analysis of PPI clustering networks of mTOR, STAT3, and CDK6 identified some functional partners that are known regulators of GBM growth and invasive properties [ 71 , 72 , 73 , 74 ]. These PPI clustering networks were also found to be enriched in pathways and ontologies that are associated with tumor progression and drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The unfolded protein response is a process activated due to overwhelming ER stress and the inability of tumor cells to counteract it. It remains unknown at which point the UPR leads to cell death, how it promotes cellular apoptosis, and/or when it promotes cell survival [ 41 ]. UPR has long been viewed as an adaptive program to sustain cellular homeostasis to counterbalance ER stress.…”
Section: Unfolded Protein Response (Upr): One Process Two Impactsmentioning
confidence: 99%